2020
DOI: 10.1029/2019jb017988
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Detection of Very Low Frequency Earthquakes Off the Hokkaido and Tohoku Pacific Coasts, Northeastern Japan

Abstract: Very low frequency earthquakes (VLFEs), classified as one type of slow earthquake, occur near seismogenic zones and can be a proxy for interplate slow slip. We investigated VLFE activity off the Hokkaido and Tohoku Pacific coasts, where the Pacific plate subducts under the North American plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(79 citation statements)
references
References 43 publications
3
75
1
Order By: Relevance
“…Generally, the detection procedure used for VLFEs was the same as that reported in Baba et al (2020). We placed 196 virtual epicentral grids on the Philippine Sea Plate boundary in Southwest Japan (Figure S1 in the supporting information) in intervals of 0.3° and computed synthetic waveforms for the 10 stations closest to each virtual source grid using the open‐source finite difference method code (OpenSWPC; Maeda et al, 2017) and by using a three‐dimensional velocity structure model of the Japan Integrated Velocity Structure Model (JIVSM; Koketsu et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the detection procedure used for VLFEs was the same as that reported in Baba et al (2020). We placed 196 virtual epicentral grids on the Philippine Sea Plate boundary in Southwest Japan (Figure S1 in the supporting information) in intervals of 0.3° and computed synthetic waveforms for the 10 stations closest to each virtual source grid using the open‐source finite difference method code (OpenSWPC; Maeda et al, 2017) and by using a three‐dimensional velocity structure model of the Japan Integrated Velocity Structure Model (JIVSM; Koketsu et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…They reported that a segmentation likely caused to cease the coseismic rupture of the 2011 Tohoku earthquake, which provides important information for a risk assessment from future major earthquakes. Baba et al (2020) detected very low frequency earthquakes (VLFEs) off the Hokkaido and Tohoku Pacific coasts by a matched-filter technique. They pointed out that their spatial distribution is consistent with the afterslip of the 2003 Tokachi-Oki earthquake (M W 8.0).…”
Section: Introductionmentioning
confidence: 99%
“…Seismic moment rates of shallow VLFEs that accompany shallow tremors were estimated by comparing the synthetic VLFE waveforms with the observed waveforms in a frequency band of 0.02-0.05 Hz using three-component seismograms from 10 F-net stations located close to the hypocenter of the VLFEs (Baba et al, 2020a). Synthetic VLFEs were calculated with OpenSWPC (Maeda et al, 2017) using the three-dimensional seismic velocity structure from the Japan Integrated Velocity Structure Model (Koketsu et al, 2012), the seismic moment tensor from the subducting plate model (Nakajima & Hasegawa, 2006;Nakajima et al, 2009;Kita et al, 2010), and the NUVEL-1A plate motion model (DeMets et al, 1994).…”
Section: Slow Earthquake Catalogs and Seismic Datamentioning
confidence: 99%
“…To discard bad estimations due to low signal to noise ratios, we excluded results with average cross correlation coefficients less than 0.25. This threshold is comparable to the threshold of VLFE detection using the matched filter technique of Baba et al (2020a). As the VLFE catalog of Nakano et al (2016Nakano et al ( , 2018 already includes information on the seismic moment rates, we applied this method only to the Japan Trench.…”
Section: Slow Earthquake Catalogs and Seismic Datamentioning
confidence: 99%
See 1 more Smart Citation